USING CHATGPT TO MENTOR PARENTS IN ENHANCING LANGUAGE DEVELOPMENT FOR CHILDREN WITH ASD 2-5 YEARS OLD THROUGH HOME-BASED DAILY ACTIVITIES IN THE VIETNAMESE CONTEXT (Proceedings of International Conference on Special Education, 2025)
ChatGPT has been rapidly and wisely applied in many areas of education. With an aim to explore the mentor’s function of ChatGPT for parents of children with ASD to promote their language at home, this research investigates how ChatGPT supports parents in designing personalized, practical and readily applicable routines for their special-needs children while also assisting them in addressing unexpected obstacles that arise during the implementation of ChatGPT’s recommended tasks. 50 volunteers were divided into two groups whose were examined to compare and analyze the benefits and challenges of language development for children with ASD 2-5 years old via home-based experiences in Haiphong City, Vietnam. One group involved the use of ChatGPT at least 3 hours a day for mentoring purposes, whereas the other group had no ChatGPT intervention. Parents participated in two sessions. The first session focused on parents’ self-discovery with ChatGPT. After two weeks, semi-structured interviews were conducted on five topics: applicability, accuracy, accessibility, diversity, and cost-effectiveness to explore the potential of the universal function of ChatGPT. In the second session, held four weeks later, based on the reflection of prior experiences from the first stage, an appropriate plan was developed to train parents on applying effective commands and fostering creativity in their interaction with ChatGPT. Input and output data on children’s language development levels were collected using the MacArthur-Bates Communicative Development Inventories test. The findings reveal that while parents demonstrate a clear understanding of the study’s objectives, certain specific requirements still need to be addressed to develop effective learning and mentoring skills. Proved to be a valuable mentoring tool, ChatGPT enables parents to overcome communication barriers, improve the quality of social interactions, support learning, and foster independence. Overall, this AI contributes significantly to empowering parents to raise their children in a linguistically enriched environment within the Vietnamese context.